Enhancing digital learning through Open-Source computer tools: an alignment with the DigComp framework - Kanso, Houssam; Gueye, Mamadou Lamine; Roig, Pedro Juan (Frontiers in Computer Science, 2025)
Nowadays, the acquisition of digital competence is essential with the ongoing digital transformation. These digital competences can be gained with the help of various dedicated tools in a direct or indirect way. In this paper, we map open-source tools with the five competence areas defined by the Digital Competence Framework (DigComp) to facilitate the development of digital skills among citizens and resources for enhancing digital competence. By proposing quantitative and qualitative studies, the paper categorizes tools based on competences and contributes to the identification of areas where tools may be lacking. Furthermore, this research aims to bridge the gap between digital competence frameworks and available open-source tools. Results show a lack in open-source tools that help citizens to gain different skills, in particular the ones related to digital safety and digital problem-solving. In addition, the study highlights the need for the development of open-source tools that target specifically toward lacking digital skills among citizens.